2009
DOI: 10.1523/jneurosci.4153-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Specific Adaptation in the Inferior Colliculus of the Anesthetized Rat

Abstract: To identify sounds as novel, there must be some neural representation of commonly occurring sounds. Stimulus-specific adaptation (SSA) is a reduction in neural response to a repeated sound. Previous studies using an oddball stimulus paradigm have shown that SSA occurs at the cortex, but this study demonstrates that neurons in the inferior colliculus (IC) also show strong SSA using this paradigm. The majority (66%) of IC neurons showed some degree of SSA. Approximately 18% of neurons showed near-complete SSA. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
450
5
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(498 citation statements)
references
References 53 publications
40
450
5
3
Order By: Relevance
“…This, with all caution in comparing different neural scales, makes the RP a possible human electrophysiological counterpart of SSA, with which it shares many properties: both occur without overt attention to sounds, are stimulus-specific, and develop rapidly over multiple timescales (Baldeweg, 2007;Nelken and Ulanovsky, 2007;CostaFaidella et al, 2011). Although SSA literature is overwhelming (Ulanovsky et al, 2003(Ulanovsky et al, , 2004Pérez-González et al, 2005;Reches and Gutfreund, 2008;Anderson et al, 2009;Malmierca et al, 2009;Antunes et al, 2010;Farley et al, 2010;Zhao et al, 2011), to date, no study has attempted to explore SSA-timing interactions. To confirm that an irregular timing dampens the repetition effects on a neuronal scale, further research in animal models tapping the influence of timing predictability in the generation of SSA should prove instructive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, with all caution in comparing different neural scales, makes the RP a possible human electrophysiological counterpart of SSA, with which it shares many properties: both occur without overt attention to sounds, are stimulus-specific, and develop rapidly over multiple timescales (Baldeweg, 2007;Nelken and Ulanovsky, 2007;CostaFaidella et al, 2011). Although SSA literature is overwhelming (Ulanovsky et al, 2003(Ulanovsky et al, , 2004Pérez-González et al, 2005;Reches and Gutfreund, 2008;Anderson et al, 2009;Malmierca et al, 2009;Antunes et al, 2010;Farley et al, 2010;Zhao et al, 2011), to date, no study has attempted to explore SSA-timing interactions. To confirm that an irregular timing dampens the repetition effects on a neuronal scale, further research in animal models tapping the influence of timing predictability in the generation of SSA should prove instructive.…”
Section: Discussionmentioning
confidence: 99%
“…In the auditory system, repetition suppression spans multiple spatial and time scales, as revealed by animal single-cell recordings exhibiting stimulus-specific adaptation (SSA) in cortical and subcortical structures (Ulanovsky et al, 2003(Ulanovsky et al, , 2004Pérez-González et al, 2005;Reches and Gutfreund, 2008;Anderson et al, 2009;Malmierca et al, 2009;Antunes et al, 2010;Farley et al, 2010;Zhao et al, 2011), human long-and middle-latency auditory-evoked potentials (AEP) (Haenschel et al, 2005;Slabu et al, 2010;Costa-Faidella et al, 2011;, and fMRI studies (Mutschler et al, 2010). However, none of the abovementioned studies explored the influence of timing regularity on repetition suppression, a subject lightly tapped in human electrophysiology literature, leading to contradictory findings.…”
Section: Introductionmentioning
confidence: 99%
“…1). Therefore, this phenomenon has been suggested as a single-unit neural correlate of the detection of unexpected stimuli (i.e., change detection, sometimes known as novelty detection; Ulanovsky et al 2003;Perez-Gonzalez et al 2005;Malmierca et al 2009). …”
Section: Stimulus-specific Adaptationmentioning
confidence: 99%
“…In SSA, we expect a stronger response every time the sequence is switched from one stimulus to the other (lower histogram in (c)) et al 2006), and auditory (Perez-Gonzalez et al 2005) pathways. In the auditory system, neurons sensitive to deviations were found at different levels of the pathway: in the inferior colliculus, the auditory thalamus and the auditory cortex (Malmierca et al 2009;Anderson et al 2009;Farley et al 2010;Antunes et al 2010;Ulanovsky et al 2004). Detailed characterization of SSA in the auditory system revealed that it is highly sensitive to minute deviations from the standard frequency.…”
Section: Stimulus-specific Adaptationmentioning
confidence: 99%
“…regains the neural response (Sobotka and Ringo, 1994;Ulanovsky et al, 2003;Katz et al, 2006;Reches and Gutfreund, 2008). This phenomenon has recently attracted scientific interest, particularly in the auditory system (Nelken and Ulanovsky, 2007;Anderson et al, 2009;Malmierca et al, 2009;Farley et al, 2010). It has been suggested to play a role in auditory scene analysis, optimal coding, and novelty detection (Ulanovsky et al, 2004).…”
Section: Introductionmentioning
confidence: 99%